Literary Literacy in High School Through the Study of Intrinsic and Extrinsic Elements in the Novel Si Anak Pemberani by Tere Liye - Rahmah Purwahida; Zulfa Sabila (2022)
The analysis of this novel aims to describe the intrinsic and extrinsic elements of Si Anak Pemberani (SAP) novel by Tere Liye and the implications in learning literature in junior high school. This research used descriptive qualitative with content analysis. The results show that the theme in the SAP novel is child courage to defend her village; using a progressive plot by offering the setting of the place, time, and atmosphere; the character's personality is displayed based on dramatic technique; using the main character's viewpoint; a comparative figure of speech as language style, contradiction, satire, and affirmation; there are mandates to protect the environment and love parents, as well as extrinsic elements in the form of the author's cultural, economic, religious, and political background and values displayed.